Athens and Attica in prehistory : proceedings of the International Conference, Athens, 27-31 May 2015 - Papadēmētriu, Nikolas; Papadēmētriu, Nikolas; Wright, James C.; Wright, James C.; Fachard, Sylvian; Fachard, Sylvian; Polychronakou-Sgouritsa, Naya; Polychronakou-Sgouritsa, Naya; Andrikou, Eleni; Andrikou, Eleni (Archaeopress Archaeology, 2020)
This resource provides the most complete overview of the Attica region from the Neolithic to the end of the Late Bronze Age. It paves the way for a new understanding of Attica in the Early Iron Age and indirectly throws new light on the origins of what will later become the polis of the Athenians